Handbook of improving performance in the workplace. Vol. 2 - Leigh, Doug; Watkins, Ryan (Preiffer essential resources for training and HR professionals, 2010)
Suitable for instructional design professionals, this book presents standard principles, and evidence-based best practices for designing instruction delivering training. It includes such topics as Interventions at the Worker Level; Interventions at the Work Team Level; and, Interventions at the Workplace and Organizational Level